2019
DOI: 10.1108/ijchm-01-2018-0039
|View full text |Cite
|
Sign up to set email alerts
|

Can revenue management be integrated with customer relationship management?

Abstract: Purpose The purpose of this study is to understand how and to what extent Hong Kong hotels have integrated customer relationship management (CRM) into their revenue management (RM) practices at individual customer level. Method Semi-structured interviews were used to gather information from experienced interviewees holding hotel RM- and marketing-related executive positions. In total, 11 revenue and 9 marketing executives were interviewed in 2016-2017 over a period of 13 weeks. The data were transcribed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…It is therefore preferable to conceptually define perceived unfairness as a multi-dimensional construct. Adopting a multi-dimensional approach enables us to comprehend perceived unfairness both in its entirety and diversity with reference to different consumer profiles (Denizci Guillet and Shi, 2019) and the different contexts of transactional exchanges.…”
Section: Theoretical Foundations Of Price Fairness and Unfairnessmentioning
confidence: 99%
“…It is therefore preferable to conceptually define perceived unfairness as a multi-dimensional construct. Adopting a multi-dimensional approach enables us to comprehend perceived unfairness both in its entirety and diversity with reference to different consumer profiles (Denizci Guillet and Shi, 2019) and the different contexts of transactional exchanges.…”
Section: Theoretical Foundations Of Price Fairness and Unfairnessmentioning
confidence: 99%
“…The research by Denizci Guillet and Shi (2019) investigated the extent to which Hong Kong hotels have merged their CRM and revenue management systems. The findings revealed that integrating revenue management systems and CRM can improve customer relationships.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Similarly, CRM can leverage the possibilities offered by Revenue Management to identify the market segments in which to prioritize marketing actions and establish long-term relationships. Hence, the simultaneous implementation of CRM and Revenue Management will be a key success factor for firms (Denizci Guillet & Shi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Hendler & Hendler, 2004;Vaeztehrani, Modarres, & Aref, 2015;Vinod, 2008). One very recent study, by Denizci Guillet and Shi (2019), offers a theoretical framework and a qualitative study that identifies the key factors in the effective strategic integration of Revenue Management and CRM. However, to date, the literature has not provided empirical evidence of the effects of this strategic combined approach on hospitality firm performance (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation